Effect of Thickness and Fibre Volume Fraction on Impact Resistance of Steel Fibre Reinforced Concrete (SFRC) - Muda Z.C.; Usman F.; Syamsir A.; Yang C.S.; Mustapha K.N.; Beddu S.; Thiruchelvam S.; Kamal N.L.M.; Alam M.A.; Birima A.H.; Itam Z.; Zaroog O.S. (Institute of Physics Publishing, 2023)
Concrete slabs; Concretes; Drops; Fiber reinforced materials; Fibers; Reinforced concrete; Shotcreting; Volume fraction; Drop weight impact; Fibre volume fraction; Impact performance; Linear correlation; Non-linear relationships; Percentage of volume; Projectile tests; Steel fibre reinforced concrete; Steel fibers; correlation; height; performance assessment; reinforced concrete; research work; size; steel; testing method; volume; weight